(untitled) (Malay Literature, 2014)
Abdullah bin Abdul Kadir or Munsyi Abdullah is a respected figure who is often associated with his standing as the Father of Modern Malay Literature as compared to Hamzah Fansuri. He has become one of Hadijah Rahmat’s focal point in her works; whether in her academic research or in creative works. Among others, this paper focused on the standing of Abdullah Munsyi which explains her leaning towards him. This is gleaned through her academic works, for example on what she has deduced from Antara Dua Kota (Between Two Cities: Tracing the works of Munsyi Abdullah in Melaka and Singapore (1999), In search of Modernity A Study of Concepts of Literature, Authorship and Notions of Self in Traditional Malay Literature (2001) or Mengukir Air di Pesisir Sastera Melayu/Indonesia Dalam Arus Jagat (2005). The same applies in the poetry collection Di Tengah Alam (At the Center of Nature (1998)), the Drama Munsyi (1998) or Kurnia Alam (Gift of Nature (2013)) that was crafted by Hadijah Rahmat; the personality of Munsyi Abdullah which she attempted to discover. This paper shows the link between the two figures in representing among others the continuity of relationship between Malay literature in Malaysia and Singapore. Keywords: Abdullah bin Abdul Kadir, Munsyi Abdullah, Hadijah Rahmat, Malay Literature, Malaysian Literature, Singaporean Literature